Effectiveness and legitimacy of Amicus Curiae submission before WTO judiciary organs - Rezana Konomi; Dorina Gjipali; Ntastin Perola (Academicus International Scientific Journal, 2023)

(untitled)
‘Amicus curiae’ is a latin term that means a ‘friend of the court’. In essence, this term encapsulates “[a] person who is not a party to a lawsuit but who petitions the court or is requested by the court to file a brief in the action because that person has a strong interest in the subject matter’’. This presents a non-party with the opportunity to submit its views regarding the outcome of a particular dispute regarding a broad range of issues (e.g. the appraisal of the merits in light of contemporary developments, the submission of factual elements etc.). These submissions have been present also during the predecessor of the current institutionalized WTO, namely the GATT system, albeit never being considered by those panels. However, there was gradual a shift in the panels’ position regarding the engagement with amicus curiae submissions. In this regard, the first amicus curiae submission in the US - Gasoline case was rejected by the WTO panel of that case. It was only the US - Shrimp case that paved the way for amicus curiae to find their way into the WTO adjudicative system. This was followed by a great polarization regarding the legitimacy of engaging with submission of non-state actors in an inherently inter-governmental system. This paper, therefore, sustains that the amicus curiae submissions facilitate effectiveness if exercised within the constraints of legitimacy (as conceptualized within the ambit of the WTO), by framing the analysis through doctrinal discussions as well as empirical evidence that is derived from other research that is appropriately referenced.